An acute bout of whole body passive hyperthermia increases plasma leptin, but does not alter glucose or insulin responses in obese type 2 diabetics and healthy adults. (July 2016) - Rivas, Eric; Newmire, Dan E.; Crandall, Craig G.; Hooper, Philip L.; Ben-Ezra, Vic
Abstract: Acute and chronic hyperthermic treatments in diabetic animal models repeatedly improve insulin sensitivity and glycemic control. Therefore, the purpose of this study was to test the hypothesis that an acute 1 h bout of hyperthermic treatment improves glucose, insulin, and leptin responses to an oral glucose challenge (OGTT) in obese type 2 diabetics and healthy humans. Nine obese (45±7.1% fat mass) type 2 diabetics (T2DM: 50.1±12y, 7.5±1.8% HbA1c) absent of insulin therapy and nine similar aged (41.1±13.7y) healthy non-obese controls (HC: 33.4±7.8% fat mass, P <0.01; 5.3±0.4% HbA1c, P <0.01) participated. Using a randomized design, subjects underwent either a whole body passive hyperthermia treatment via head-out hot water immersion (1 h resting in 39.4±0.4 °C water) that increased internal temperature above baseline by ∆1.6±0.4 °C or a control resting condition. Twenty-four hours post treatments, a 75 g OGTT was administered to evaluate changes in plasma glucose, insulin, C-peptide, and leptin concentrations. Hyperthermia itself did not alter area under the curve for plasma glucose, insulin, or C-peptide during the OGTT in either group. Fasting absolute and normalized (kg·fat mass) plasma leptin was significantly increased ( P< 0.01) only after the hyperthermic exposure by 17% in T2DM and 24% in HC groups ( P <0.001) when compared to the control condition. These data indicate that an acute hyperthermic treatment does not improve glucose tolerance 24 h post treatment in moderate metabolic controlled obese T2DM or HC individuals.